2023
DOI: 10.1029/2022jd038373
|View full text |Cite
|
Sign up to set email alerts
|

Shifts of Formation Regimes and Increases of Atmospheric Oxidation Led to Ozone Increase in North China Plain and Yangtze River Delta From 2016 to 2019

Abstract: Air pollution poses a great threat to public health and ecological systems in China, especially in the North China Plain (NCP) and Yangtze River Delta (YRD) Zhang, Xue, et al., 2021). Specifically, PM 2.5 (fine particulate matter with an aerodynamic diameter less than 2.5 μm) and O 3 were associated with ∼630,000 and ∼300,000 annual premature deaths in China from 2010 to 2015, respectively (Malley et al., 2017;G. Zhu et al., 2019), and induced severe damage to crop yields (Zhang, Yue, et al., 2021). Aiming to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 75 publications
(141 reference statements)
0
1
0
Order By: Relevance
“…Previous studies reported that atmospheric oxidation capacity (AOC) was a better indicator to characterize the synergy capacity of the chemical reactions leading to PM 2.5 and O 3 formation. , Hence, we estimated the diel variation of AOC in three pollution types as shown in Figure b–e. The average total AOC (T-AOC) during the O 3 pollution period (2.7 × 10 7 molecules cm –3 s –1 ) is higher than the average T-AOC in China (2.2 × 10 7 molecules cm –3 s –1 ), indicating the highly oxidative environment.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that atmospheric oxidation capacity (AOC) was a better indicator to characterize the synergy capacity of the chemical reactions leading to PM 2.5 and O 3 formation. , Hence, we estimated the diel variation of AOC in three pollution types as shown in Figure b–e. The average total AOC (T-AOC) during the O 3 pollution period (2.7 × 10 7 molecules cm –3 s –1 ) is higher than the average T-AOC in China (2.2 × 10 7 molecules cm –3 s –1 ), indicating the highly oxidative environment.…”
Section: Resultsmentioning
confidence: 99%